Homeless Shelter Use and Reincarceration Following Prison Release - Culhane, Dennis P (Criminology & public policy, 2004)
This paper examines the incidence of and interrelationships between shelter use and reincarceration among a cohort of 48,424 persons who were released from New York State prisons to New York City in 1995-1998. Results show that, within two years of release, 11.4% of the study group was again imprisoned. Using survival analysis methods, time since prison release and history of residential instability were the most salient risk factors related to shelter use, and shelter use increased the risk of subsequent reincarcerations